1-Bromoethene-1-sulfonyl fluoride (1-Br-ESF), a new SuFEx clickable reagent, and its application for regioselective construction of 5-sulfonylfluoro isoxazoles. Issue 35 (16th April 2018) - Leng, Jing; Qin, Hua-Li
Abstract : A unique SuFEx clickable tris-electrophile, 1-Br-ESF, was developed and applied for the synthesis of 5-sulfonylfluoro isoxazoles with exclusive regioselectivity. Abstract : A new fluorosulfonylation reagent 1-bromoethene-1-sulfonyl fluoride was developed (1-Br-ESF). This unique reagent possesses three addressable handles (vinyl, bromide, and sulfonyl fluoride) and has great potential to function as a tris-electrophile and as a sulfur(vi ) fluoride exchange (SuFEx) clickable material to enrich the SuFEx tool cabinet. The application of this reagent for regioselective synthesis of 5-sulfonylfluoro isoxazoles has been realized through a [3+2] cycloaddition with N -hydroxybenzimidoyl chlorides. This practical protocol provides a general and direct route to functionalized isoxazoles possessing sulfonyl fluoride moieties.